MODELING OF OVER VOLTAGES IN 10 kV CABLE DISTRIBUTION NETWORK AT SINGLE-PHASE FAULTS TO GROUND WITH ARC - Bosneaga V.A; Postolaty V.M.; Suslov V.M.; Klinduhov A.N. (Problems of the Regional Energetics)
The aim of the work is to study surges in the 10 kV cable distribution network in the presence (occurrence) of the intermittent arc, which could lead to significant damages in the network, including the failure of distribution transformers. Surge analysis is performed for single-phase to ground faults in the network. Surges’ levels in the 10 kV distribution network were determined for single-phase-to-ground faults and for HV winding inter-turn fault in the 10/0,4 kV distribution transformer. It is shown, that the maximum surge values are determined mainly by the functioning of installed surge arresters and are not directly related to the presence of the arc elimination reactor, which acts mainly as the current limiter in the place of short-circuit and only smoothes high-frequency oscillations. The elaborated model may be used for analyses of surges in the cable network, caused by short circuits via (due to) the intermittent arc.